Eco-Friendly Synthesis, Antibacterial Activity, and Photocatalytic Performance of Zno Nanoparticles Synthesized via Leaves Extract of Paraserianthes Lophantha - Karrar Hazim, Zaid Hamza, Lidia Mohamed, Faris j. Alyasiri (Pakistan Journal of Medical & Health Sciences, 2022)
This study included the synthesis in environmentally friendly nanotechnologies using the leaf extract of the plant Paraserianthes lophantha. This eco-friendly method is safe and non-toxic or harmful to the environment. The method is economical, easy to operate, and highly efficient, and the properties of the resulting compounds can be controlled, in this way the ZnO compound can be controlled with the same plant extract and by the reaction. The research also included the result and study of the properties of these nanoparticles through various techniques including Field emission-scanning electron microscopic (FE-SEM) X-ray diffraction XRD. atomic force microscopy(AFM).Transmission electron microscopic studies (TEM). Also, the analysis of ZnO NPs was investigated by EDX-mapping and confirmed the existence and efficient degradation of Zn, O in the composite. The efficacy study of the prepared compound using bacteria was used. The activity of ZnO NPs and their effect on antibacterial was studied using two different types of bacteria, Gram negative E. Coli and Gram positive S.aureus e. Also, the photocatalytic ability of ZnO NPs was identified through the photodegradation process of the dyes, as the rhodamine B dye was degraded, and the rate of degradation was 83%. The effect of the amount of the catalyst was studied and quantities (0.2,0.4,0.6,0.8,1, 1.2,1.4,1.6g/L) and the best weight was 1gm and the dye concentration was 10ppm. receivers for electrons as well as those electrons and free holes are working on water and oxygen conversion to .OH radical with very powerful oxidation.